A study of irradiation damage in iron and Fe-Cr alloys - Xu, S (2013)
Irradiation damage structures induced in pure Fe and Fe-Cr (up to 14%Cr) alloys by 2 MeV Fe+ ion irradiations in the temperature range 300-460°C were investigated by transmission electron microscopy. Specimens were irradiated in bulk to doses of 1.5 x 1019 Fe+/m2 (about 2.5 displacements per atom: dpa) and 4.5 x 1019 Fe+/m2 (about 7 dpa). In most cases, damage took the form of dislocation loops with diameters from 2-100nm; the loops were distributed uniformly within all the samples. At higher irradiation temperatures (400°C, 460°C), complex microstructures such as finger loops (50nm in width and 1 micron in length) and perpendicular <100> loop clusters, were observed in both pure Fe and Fe-Cr samples. Loop sizes and densities were seen to change as a function of irradiation temperature and dose. Loop sizes were seen to increase as the increase of irradiation temperatures and doses, while loop densities only increased with increasing doses and decreased as increasing temperatures. Loops with both types of Burgers vectors (<100> and ½<111>) were observed in all the samples. The proportion of <100> loops was higher in Fe than that in Fe-Cr alloys at the same irradiation condition, which has can be attributed to the high mobility of ½<111> loops in Fe, so that a large proportion of them will escape to the (001) foil surface. A transition in loop Burgers vectors as a consequence of increasing temperature was observed. In Fe, the proportion of <100> loops increased with increasing irradiation temperature from 40% at 300°C to 60% at 460°C. A similar trend was found in the Fe-Cr alloys, but due to the higher proportion of ½<111> loops in these alloys, the increase of <100> loops was not that obvious, being from 30% at 300°C to 45% at 460°C(Fe-11Cr). The effects of irradiation dose rate on the formation of dislocation loops by 2 MeV Fe+ ions were also investigated. These irradiations were carried out at 300°C with two different implantation dose rates: 6 x 10-4 dpa/s and 3 x 10-5 dpa/s. The implantation dose for both implantations was 0.38 x 1019 Fe+/m2 (0.5 dpa). Both the average loop size and loop densities for the Fe-Cr specimens subjected to the high dose rate irradiation were higher than that in the low dose rate irradiations. Take Fe-14Cr as an example, that the loop densities in high dose rate irradiation increased about 90% compared to that in low dose rate, and the average loop size in high dose rate irradiation was 30% larger than that in low dose rate irradiation. The ‘inside-outside contrast’ method was applied to determine the loop nature in all the samples. It was found that all the large loops (>5nm) are of interstitial type. Any vacancies are believed to exist in the form of small dislocation loops (<5nm) or sub-microscopic voids.